Analysis of The Effect of Brand Image and Perceived Quality on Customer Loyalty Through Customer Satisfaction as an Intervening Variable (Case Study PT. Sempurna Sukses Sejati) - sherly, Sherly (SEEIJ (Social Economics and Ecology International Journal), 2022)
To improve the company's performance in overcoming the tight competition in the stationery industry at this time, research should be conducted on how the brand image of ESCO products in the minds of consumers and how the perception of the quality of ESCO products according to consumers who use them. This research was conducted to find out how far the ESCO brand products have developed in the community and whether they can compete in the market with various brands and similar products. Therefore, this study also wants to analyse the extent to which consumers are loyal to the brand and how far the satisfaction has been obtained. Consumer satisfaction is something that can encourage consumers to be more loyal to a brand and consumer loyalty to the brand is very important for the company because it will bring long-term profit and benefits to the company's products in the future.